(untitled) (Canadian Eye Care Today, 2023)
Anti-vascular endothelial growth factor (VEGF) is the mainstay of treatment for several visually debilitating diseases and is considered the standard of care for a number of conditions which may affect younger patients, including women of childbearing age. These commonly include, but are not restricted to, diabetic macular edema (DME), proliferative diabetic retinopathy (PDR) and myopic choroidal neovascularization (CNV). As in other areas of medicine, pregnant and breastfeeding women are often excluded from clinical trials due to the unknown side effect profile of new drugs. This lack of evidence regarding the safety of anti-VEGF agents in pregnancy and breastfeeding introduces challenges for clinicians seeking to counsel these patients, particularly because anti-VEGF injections may be often used for an extended period of time, depending on the nature of the retinal disease. As a precaution, anti-VEGF injections are generally not recommended for women who are either pregnant or breastfeeding, given that they are considered Category C drugs and there is limited data regarding their excretion in human breast milk. Therefore, treatment of this group of patients is typically managed on a case-by-case basis, balancing the potential patient benefits with safety concerns for the infant.